Delivery mechanisms and impact of training through microfinance - Ranjula Bali Swain; Adel Varghese (Uppsala University, Department of Economics, 2011)
We evaluate the effect of delivery mechanisms for training provided by facilitators of self help groups (SHGs). Indian SHGs are unique in that they are mainly NGO-formed microfinance groups but later funded by commercial banks. We correct for both membership and training endogeneity. Training impacts assets but not income. Underlying conditions that benefit training include better infrastructure (as in paved roads), linkage model type, and training organizer.
urn:nbn:se:uu:diva-153348
Keywords: G21; I32; O12; 330; Asia; India; microfinance; impact studies; training; Self Help Groups; Selbsthilfeförderung (Entwicklungsländer); Mikrofinanzierung; Wirkungsanalyse; Indien